Removal of dye from wastewater of textile industry using banana stem-derived biochar / Wen Chang Qi - Wen , Chang Qi (2017)
Banana stem is a natural, low-cost agricultural by-product in Malaysia which has been studied for its potential application as an adsorbent in its raw and biochar form to remove methylene blue (MB) and congo red (CR) dyes from aqueous solution. The banana stem was carbonized at various temperatures (300-700°C) using the muffle furnace with limited oxygen conditions. The experiments were conducted by using the batch adsorption technique under different conditions of adsorbents dosage, initial dye concentration, contact time, agitation speed, solution pH, and temperature on the removal of MB. The characteristics of adsorbents were determined by using BET, FTIR, SEM and proximate analysis. The adsorption isotherms of Langmuir and Freundlich were employed to examine the equilibrium adsorption data. The adsorption kinetics of pseudo-first-order and pseudo-second-order were employed to explore the mechanism of adsorption. Thermodynamic parameters such as the changes in ΔG, ΔH and ΔS were also determined. Desorption studies were carried out in order to further study the stability of MB adsorbed on the adsorbent. The results showed that biochar produced at 700°C (BC700) is the best in removing MB as it can achieve maximum removal percentage of more than 98% due to it has high surface area, high porosity, and high fixed carbon content. The adsorption of MB can be best described by Langmuir isotherm and the pseudo-second order kinetic model and the adsorption process was found to be exothermic for biochars (BC300 and BC700) and endothermic for raw banana stem. The desorption study indicated that the dye was firmly adsorbed onto the biochar. Thus, all results indicated that biochars prepared from banana stem adsorbed MB efficiently and could be employed as a low cost alternative in wastewater treatment for the removal of cationic dyes.